2014
DOI: 10.1371/journal.pcbi.1003414
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Antigen between Th1 and Th2 Responses Determines the Timing of the Immune Response Switch during Mycobaterium avium Subspecies paratuberulosis Infection in Ruminants

Abstract: Johne's disease (JD), a persistent and slow progressing infection of ruminants such as cows and sheep, is caused by slow replicating bacilli Mycobacterium avium subspecies paratuberculosis (MAP) infecting macrophages in the gut. Infected animals initially mount a cell-mediated CD4 T cell response against MAP which is characterized by the production of interferon (Th1 response). Over time, Th1 response diminishes in most animals and antibody response to MAP antigens becomes dominant (Th2 response). The switch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 69 publications
0
46
1
Order By: Relevance
“…Additionally, the progression of mycobacterial infection has been thought to be related to Th1 / Th2 migration of the host (13). In the early stage of infection, the cell-mediated CD4 + T cell response (Th1 response) to MAP is displayed (13). Th1 response decreases as the disease progresses, but the antibody response (Th2 response) to MAP increases (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the progression of mycobacterial infection has been thought to be related to Th1 / Th2 migration of the host (13). In the early stage of infection, the cell-mediated CD4 + T cell response (Th1 response) to MAP is displayed (13). Th1 response decreases as the disease progresses, but the antibody response (Th2 response) to MAP increases (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of infection, the cell-mediated CD4 + T cell response (Th1 response) to MAP is displayed (13). Th1 response decreases as the disease progresses, but the antibody response (Th2 response) to MAP increases (13). Thus, since the Th1 / Th2 shift is related to disease progression and bacterial excretion, many studies have determined the MAP infection stage based on detection of MAP and MAP-specific antibody in specimen such as feces, milk, and sera (12,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately it is still unclear what is driving the shift in this model. A recent mathematical modeling study on the Th1/Th2 paradigm indicated that initial dose and bursting size control the timing of the switch [ 73 ]. Most of the data underlying these models were derived from PBMC and serum derived from animals in cross sectional studies usually in a setting of optimizing diagnosis of paratuberculosis.…”
Section: Adaptive Immunity During Paratuberculosis Infectionmentioning
confidence: 99%
“…Computational methods have also been applied to study the plasticity of CD4+ T cells. Magombedze et al considered a population plasticity mechanism between Th1 and Th2 during Mycobacterium avium infection by using a reduced ODE-based model where the phenotype change of MAP-specific T cells occurred due to differences in the rates of differentiation, proliferation, and death at the site of infection (Magombedze et al, 2014 ). However, the cellular plasticity involving several intracellular pathways was not represented.…”
Section: Deciphering Cd4+ T Cell Plasticity By Using Computational Momentioning
confidence: 99%